Acute hemodynamic responses during resistance exercises associated with blood flow restriction: a systematic review (Research, Society and Development, 2022)
Resistance exercise associated with blood flow restriction has been shown to be an effective metd for hypertrophy and muscle strength gain. Analyse the acute hemodynamic responses after resistance exercise associated with the blood flow restriction method. For this, a systematic review was conducted according to the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analysis). The databases used for the literature search were PubMed and Web of Science, using the following descriptors: blood flow restriction AND hemodynamic responses OR hemodynamic monitoring OR blood pressure OR cardiac output OR heart rate OR vascular resistance. Studies that analysed acute hemodynamic responses after a resistance exercise session associated with blood flow restriction were included in this systematic review. Eleven studies that evaluated hemodynamic variables were included. The systematic analysis of the results indicates that resistance physical exercise associated with blood flow restriction results in an immediate increase in blood pressure levels and heart rate (HR). In the analysed studies, ten experimental designs assessed systolic (SBP), diastolic (DBP) and mean blood pressure (MBP). Of these, seven, eight and nine experimental designs showed significant increases in these variables, respectively. Based on the PEDro scale, five studies were classified as articles with low risk of bias, while the other six were classified as medium risk of bias. Based on the results found, it is concluded that resistance exercise associated with blood flow restriction tends to promote significant increases in hemodynamic variables, such as SBP, DBP, MAP and HR.